2019
DOI: 10.3390/mi10120853
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Pulsed He–Ne Laser Irradiation on the Red Blood Cell Interaction Studied by Optical Tweezers

Abstract: Optical Tweezers (OT), as a revolutionary innovation in laser physics, has been extremely useful in studying cell interaction dynamics at a single-cell level. The reversible aggregation process of red blood cells (RBCs) has an important influence on blood rheological properties, but the underlying mechanism has not been fully understood. The regulating effects of low-level laser irradiation on blood rheological properties have been reported. However, the influence of pulsed laser irradiation, and the origin of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 33 publications
2
19
0
Order By: Relevance
“…With the double-beam OTs system as illustrated in Figure 4 and the above-stated methods, our group recently revealed the influence of cell interaction time (up to 300 s) on RBC disaggregation dynamics [73,102]. The results showed that the RBC disaggregation force increases with initial interaction time between two RBCs, whereas the aggregation force is independent to the cell contact time.…”
Section: Evaluation Of Dynamic Cell-cell Interaction Between Rbcsmentioning
confidence: 97%
See 3 more Smart Citations
“…With the double-beam OTs system as illustrated in Figure 4 and the above-stated methods, our group recently revealed the influence of cell interaction time (up to 300 s) on RBC disaggregation dynamics [73,102]. The results showed that the RBC disaggregation force increases with initial interaction time between two RBCs, whereas the aggregation force is independent to the cell contact time.…”
Section: Evaluation Of Dynamic Cell-cell Interaction Between Rbcsmentioning
confidence: 97%
“…The experimental samples used for general RBC measurements with OTs are erythrocytes suspensions with controlled concentrations. Normal circulating human RBCs can be obtained by washing the fingertip-prick blood drops in phosphate buffer saline [102] and for evaluation of the maturing RBCs during different development stages in erythropoiesis; the immature RBCs can be obtained by aspirating bone marrow cells from the iliac crest [103]. The cells are suspended in designed solutions for different measurement purposes, such as plasma or model solutions containing different types and concentrations of fibrous biomolecules, neutral polymers or nanoparticles.…”
Section: Rbc Preparation and Trappingmentioning
confidence: 99%
See 2 more Smart Citations
“…Two papers are concerned with the investigation of mechanical interactions of red blood cells (RBCs). Zhu et al have investigated the disaggregation of RBCs by using optical tweezers to quantify the force required to separate aggregated cells, showing that a short irradiation from a pulsed helium-neon laser may reduce the aggregation force [1]. Avsievich et al report on the effect of polymeric nanocapsules-a model for drug delivery vehicles-on the aggregation force of RBCs, finding no change and no cytotoxicity as a result of the nanocapsule treatment [2].…”
mentioning
confidence: 99%